A CRITICAL ASSESSMENT OF FREEDOM OF EXPRESSION IN A DEMOCRATIC POLITICS - Seid Ali, Mohammed (European Scientific Journal, ESJ, 2015)
According to western democracy, which demands the fundamentals of individual autonomy, freedom of expression is among those ground maxims that trigger critical and philosophical discourse. A democratic system of government, which wins popular legitimacy, is expected to lay down solid and systematic foundations with serious political will and practical commitment for the realization of “market place of ideas”. Besides, free and democratic societies, which have constitutionally stipulated rights to freely access, transfer, and choose information with diversity of sources and contents, could naturally have the better chance to pass informed decisions and judgments in cogently defining their destinies. In principle, such a democratic political system, with all its contemporary challenges, does not therefore impose up on individual citizens’ mind public media over private media, domestic media over international as well as social media, and development oriented news over diversity of ideas. Though there are varieties of literatures as well as research works conducted in this regard, little has done in critically justifying why such a system authorizes individual human agents to be indispensible and autonomous vetoes to determine the sources and the contents of information. Besides, this work tries to critically explore some of the positive developments and existential challenges posing significant threat to such a democratic value for the autonomy of individual human actors. To this effect, critical evaluation and reflection of the main philosophical assumptions on freedom of information, which in turn enable us to critically assess contemporary problems and opportunities, have been parts of this article. In this regard, however, this work has not been an attempt for generalization on topic raised based on existential situations of individual countries.